Criminal justice in Malaysia issue of delays in delivering written judgment / Muhammad Hilmi Sulaiman, Rohana Ramli and Varnessa Dimah Bonaventure. - Sulaiman, Muhammad Hilmi; Ramli, Rohana; Bonaventure, Varnessa Dimah (2008)
The issue of delays in the process of trial is not new to our society. The term 'justice delay is justice denied' has been a norm that still has validity since the establishment of court system. When the process of justice is delayed, the freedom of liberty such as the freedom of speech, freedom of movement, and the right to be heard as laid in the Federal Constitution1 are being violated. The violation of these rights has been a frequent injustice made by the judiciary division of the government. It arises from not only the trial lengthy procedure but also caused by sloppy investigations made by police in carrying out their investigation report. Lawyers also can be blamed for their part because they often to repeatedly postponed their cases. They also can be held responsible in failure to produce the petition of appeal within 14 days after the appeal record was made. Because of these reasons and their inability to cope with the arrangement of trial dates has caused their clients time and cost. The lawyer's failure to acquire cooperation from the witness and accused also brings delay to the court. This had caused the victim to be detained in jail or lock-up and witnesses to be absent on the day of hearing.